2020
DOI: 10.3390/rs12162632
|View full text |Cite
|
Sign up to set email alerts
|

Area and Mass Changes of Glaciers in the West Kunlun Mountains Based on the Analysis of Multi-Temporal Remote Sensing Images and DEMs from 1970 to 2018

Abstract: Most of the world’s glaciers have retreated significantly against the background of recent climate warming, while reports have indicated that the glaciers in the West Kunlun Mountains (WKL) may be in a relatively stable state, although there are some gaps in previous research. Based on Landsat series data, topographic maps, SRTM and TanDEM-x data, this paper extracts detailed glacial area information and glacial mass balance during different time periods from 1970 to 2018. We found that, the total area of glac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Similarly, the glacier surface elevation in this region thinned slightly from 1970 to 2000; and then, it thickened slightly after 2000 (Bao et al., 2015; Cao et al., 2020; Wang et al., 2018). Recent studies have revealed that the patterns of some of the glaciers in the WKM differ with those of others; for example, they display sudden frontal position advances and exhibit thickening and thinning at lower and higher elevations, respectively, and surface velocity increases (Cao et al., 2020; Ke et al., 2015). Such phenomena are most likely related to glacier surging (Yasuda & Furuya, 2015).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Similarly, the glacier surface elevation in this region thinned slightly from 1970 to 2000; and then, it thickened slightly after 2000 (Bao et al., 2015; Cao et al., 2020; Wang et al., 2018). Recent studies have revealed that the patterns of some of the glaciers in the WKM differ with those of others; for example, they display sudden frontal position advances and exhibit thickening and thinning at lower and higher elevations, respectively, and surface velocity increases (Cao et al., 2020; Ke et al., 2015). Such phenomena are most likely related to glacier surging (Yasuda & Furuya, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…In this study, the glacier frontal positions in each Landsat image from 1972 to 2020 have been manually digitized. In this process, glacier outlines from Cao et al (2020) and DEM (TanDEM-X) and Google Earth high-resolution images (Worldview and Pleiades images during 2000-2010) were used as references. In order to compare with the glacier surface elevation changes, the changes in glacier lengths were also divided into two time periods (before and after 2000).…”
Section: Glacier Frontal Position Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…The West Kunlun Shan (WKS) located on the northwestern Tibetan Plateau, with a glacier area of about 8817.78 km 2 , accounts for more than 70% of the total glacier area in the Kunlun Mountain [15]. During the past few decades, glaciers in the WKS have generally experienced a balanced or slightly negative mass change [16][17][18][19][20]. Over a similar time period, surge events have been detected for many glaciers in the WKS [17,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%